REFUGEE BURDEN SHARING: AN EVOLVING REFUGEE PROTECTION CONCEPT? - Arie Afriansyah; Angky Banggaditya (Arena Hukum, 2017)
AbstractThis article discusses cooperation between states as part of the international community in handling and protecting the refugees which arrive in one's territory massively, observed from international law standpoint. The concept of cooperation, which is further known as burden sharing concept, is rooted from the principle of international cooperation and international solidarity which is developing as a principle agreed by states and are widely recognized as a general principle of law. The central question is how such concept exists under international law and how is the implementation by states, especially Indonesia. It concludes that burden sharing is a concept that is still evolving so that there is no rigid guidance in the implementation yet. Therefore, there are varieties of implementation mechanisms among states. In relation with Indonesia, it needs support from other countries in handling the mass influx of refugees, especially the Rohingya refugees. Finally, this article suggests that as part of international community, states should always assert their contribution in accommodating the mass influx of refugees which certainly would very burdening if it is handled only by one state.AbstrakArtikel ini membahas kerjasama antar Negara sebagai bagian dari masyarakat internasional dalam menangani dan melindungi para pengungsi yang tiba di wilayah tertentu secara besar-besaran, berdasarkan sudut pandang hukum internasional. Konsep kerjasama, yang selanjutnya dikenal dengan konsep pembagian beban (burden-sharing), berakar dari prinsip kerjasama internasional dan solidaritas internasional yang berkembang sebagai prinsip yang disepakati oleh Negara dan dikenal secara luas sebagai prinsip umum hukum. Pertanyaan utamanya adalah bagaimana konsep tersebut di bawah hokum internasional dan bagaimana pelaksanaannya oleh negara-negara, khususnya Indonesia. Tulisan ini menyimpulkan bahwa pembagian beban (burden-sharing) adalah konsep yang masih terus berkembang sehingga belum ada panduan yang kaku dalam pelaksanaannya. Oleh karena itu, ada beberapa jenis mekanisme pelaksanaan antarnegara. Berkaitan dengan Indonesia, dibutuhkan dukungan dari negara lain dalam menangani masuknya massa pengungsi, terutama pengungsi Rohingya. Akhirnya, artikel ini menunjukkan bahwa sebagai bagian dari masyarakat internasional, Negara harus selalu memberikan kontribusi mereka dalam mengakomodasi masuknya massa pengungsi yang tentunya akan sangat membebani jika ditangani hanya oleh satu negara.